Tapinarof cream 1% once daily was well tolerated in adults and children with atopic dermatitis in two phase 3 randomized trials - Linda Stein Gold; James Del Rosso; Benjamin D. Ehst; Matthew J. Zirwas; Lawrence J. Green; Philip M. Brown; David S. Rubenstein; Stephen C. Piscitelli; Anna M. Tallman (Journal of Dermatological Treatment)
Background: Tapinarof cream 1% once daily (QD) demonstrated significant efficacy in patients down to age 2 years with atopic dermatitis (AD) in the ADORING 1 and 2 phase 3 trials. We report local tolerability outcomes.Methods: Patients received Tapinarof or vehicle cream QD for 8 weeks. Tolerability was evaluated using patient/parent/caregiver and investigator 5-point Local Tolerability Scales (LTS). Investigators assessed tolerability for sensitive skin areas, including face/neck.Results: 813 patients were randomized (∼80% pediatric). Mean pretreatment baseline overall LTS scores were similar across groups and trials: 1.0–1.9 (patient-assessed) indicating slight burning/stinging and itching; and 0.3–0.6 (investigator-assessed) indicating no-to-minimal irritation. Tapinarof was well tolerated with improvement from pretreatment baseline and no-to-minimal burning/stinging and itching from first application through Week 8 (patient-reported): mean Week 8 LTS scores were 0.2–0.4 (burning/stinging) and 0.6–0.8 (itching). Investigators reported improvement from pretreatment baseline with no-to-minimal irritation (dryness/erythema/peeling) from first Tapinarof application through Week 8 (mean LTS scores: 0.2 and 0.1 in ADORING 1 and 2, respectively). Across sensitive skin, investigators reported no-to-minimal irritation from first application through Week 8 (mean scores [Tapinarof versus vehicle]: 0–0.3 versus 0–1.0).Conclusion: Tapinarof was well tolerated locally from first application through Week 8, including on sensitive skin areas.Clinicaltrials.gov numbers NCT05014568, NCT05032859